Dyslipidemia in children with chronic kidney disease-findings from the Cardiovascular Comorbidity in Children with Chronic Kidney Disease (4C) study - Mencarelli, Francesca; Azukaitis, Karolis; Kirchner, Marietta; Bayazit, Aysun; Düzova, Ali; Canpolat, Nur; Bulut, Ipek Kaplan; Obrycki, Lukasz; Ranchin, Bruno; Shroff, Rukshana; Caliskan, Salim; Candan, Cengiz; et al. (Pediatric nephrology, 2024)
BACKGROUND: Dyslipidemia is an important and modifiable risk factor for CVD in children with CKD. - METHODS: In a cross-sectional study of baseline serum lipid levels in a large prospective cohort study of children with stage 3-5 (predialysis) CKD, frequencies of abnormal lipid levels and types of dyslipidemia were analyzed in the entire cohort and in subpopulations defined by fasting status or by the presence of nephrotic range proteinuria. Associated clinical and laboratory characteristics were determined by multivariable linear regression analysis. - RESULTS: A total of 681 patients aged 12.2 ± 3.3 years with a mean eGFR of 26.9 ± 11.6 ml/min/1.73 m2 were included. Kidney diagnosis was classified as CAKUT in 69%, glomerulopathy in 8.4%, and other disorders in 22.6% of patients. Nephrotic range proteinuria (defined by a urinary albumin/creatinine ratio > 1.1 g/g) was present in 26.9%. Dyslipidemia was found in 71.8%, and high triglyceride (TG) levels were the most common abnormality (54.7%). Fasting status (38.9%) had no effect on dyslipidemia status. Except for a significant increase in TG in more advanced CKD, lipid levels and frequencies of dyslipidemia were not significantly different between CKD stages. Hypertriglyceridemia was associated with younger age, lower eGFR, shorter duration of CKD, higher body mass index (BMI-SDS), lower serum albumin, and higher diastolic blood pressure. - CONCLUSIONS: Dyslipidemia involving all lipid fractions, but mainly TG, is present in the majority of patients with CKD irrespective of CKD stage or fasting status and is significantly associated with other cardiovascular risk factors.